CBDC & DeFi impact on traditional banking : the european reality, “Montepio Case” - Vieira, João Diogo Lebre (2022)
This dissertation explores how DeFi is emerging internationally, with a special focus on the European context, seeking to understand which are the main players, the products and instruments they offer, as well as the possible outcomes of this ecosystem, especially in relation to the banking sector. Therefore, several interviews were conducted with experts in this sector, as well as an extensive benchmarking analysis to understand the general context, as well as the possible benefits that DeFi and CBDC's may offer and if these may be beneficial to the Portuguese reality. The results of this study show that DeFi, CBDC's and blockchain related technologies promise to mark a new stage in our daily lives, being one of the great innovations capable of changing the traditional banking sector, lowering transaction costs, promoting transparency and making international transactions more efficient. Central Banks, through CBDCs can also apply monetary policies more efficiently. The benefits far outweigh the possible risks, and there is an emerging need for regulation in this new world with so much to explore.